Religious Diversity, Islam, and Integration in Western Europe—Dissecting Symbolic, Social, and Institutional Boundary Dynamics - Matthias Koenig (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Religious diversity and, in particular, the presence of Islam is often perceived as a~threat to national solidarity and social cohesion across Western Europe. Reviewing and synthesizing compartmentalized research literature on religion and immigrant integration, this article scrutinizes symbolic, social, and institutional boundary processes and their underlying micro-level mechanisms. First, it showcases the relative brightness of religiously coded symbolic boundaries that is sustained by anti-Muslim prejudices among the majority as well as by the intergenerational transmission of Muslim religiosity. Second, it discusses whether and how religious differences translate into social boundaries, through both discrimination and religiously based (self-)segregation on the labor market, in education, and in social networks. Third, it traces how interactive sequences of Muslims' claims for recognition and public policy responses have led to institutional boundary shifts under the influence of constitutional law and European human rights and anti-discrimination directives. The article concludes by discussing scenarios of how macro-level processes of symbolic, social, and institutional boundary transformation interrelate, thus raising broader questions on religious diversity and integration in Western European nation-states. – – Religiöse Diversität und insbesondere die Präsenz des Islam werden in Westeuropa oftmals als Bedrohung nationaler Solidarität und sozialer Kohäsion wahrgenommen. Gestützt auf ein Review und eine Synthese spezialisierter Forschungsliteraturen zu Religion und der Integration von Immigranten untersucht der Beitrag symbolische, soziale und institutionelle Prozesse der Grenzziehung und ihre zugrundeliegenden Mikromechanismen. Erstens dokumentiert er die relative Schärfe religiös codierter symbolischer Grenzen, die sich auf anti-muslimische Vorurteile auf Seiten der Mehrheit und die intergenerationelle Transmission muslimischer Religiosität auf Seiten der Minderheit stützt. Zweitens diskutiert er, ob und wie religiöse Differenzen –~durch Diskriminierung und religiöse (Selbst‑)Segregation~– in soziale Grenzen auf dem Arbeitsmarkt, im Bildungssektor und in sozialen Netzwerken übersetzt werden. Drittens rekonstruiert er, wie interaktive Sequenzen muslimischer Anerkennungsforderungen und öffentlicher Politik unter dem Einfluss von Verfassungsrecht und europäischen Normen von Menschenrechten und Anti-Diskriminierung zu institutionellen Grenzverschiebungen geführt haben. Der Beitrag schließt mit einer Diskussion verschiedener Szenarien, wie sich die Makroprozesse symbolischer, sozialer und institutioneller Grenzziehungen zueinander verhalten und beleuchtet damit allgemeinere Fragen von religiöser Diversität und Integration in westeuropäischen Nationalstaaten.
Keywords: 300; Boundary paradigm; Discrimination; Migration; Muslim minorities; Social integration; Diskriminierung; Grenzparadigma; Muslimische Minderheiten; Soziale Integration